KUASA MENJUAL SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA KREDIT MACET DIKECAMATAN SUKAJADI KOTA PEKANBARU - Afrian, Muhammad Eddo; Hanifah, Mardalena; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Improving standards of living, especially in the economic field can be done by encouraging the growth and development of both small-scale industries as well as large-scale as well as cooperative as the national economy. Since the birth of (UUHT) Law No. 4 Year 1996 on Mortgage then uninstall the mortgage on the collateral according to the rules of the Civil Code by using the authority to sell, but today is part of financial institutions such as banks continue to use certificate authorization to sell despite the guarantee of the debt had been installed / encumbered encumbrance and it is still run by a notary.This study aims to identify and explain the process of issuing certificate authority to sell by a notary and functions of the deed of power to sell that have been charged with security rights and protections afforded by a notary.This type of research using sociological research, which meant an immediate interview person.This study aims to identify and explain the process of issuing certificate authority to sell by a notary and functions of the deed of power to sell that have been charged with security rights and protections afforded by a notary.These results indicate procedures that have the authority to sell the encumbered encumbrance, it becomes pointless / useless. The function of the authority to sell will be effective when the debtor is given a warning after the publication of the creditors for the tort made by the debtor.Key Words:authority to sell-trouble debt–dispute resolution